2017
DOI: 10.3233/jpd-179000
|View full text |Cite
|
Sign up to set email alerts
|

Top Altmetric Scores in the Parkinson’s Disease Literature

Abstract: A new class of social web-based metrics for scholarly publications (altmetrics) has surfaced as a complement to traditional citation-based metrics. Our aim was to study and characterize those recent papers in the field of Parkinson’s disease which had received the highest Altmetric Attention Scores and to compare this attention measure to the traditional metrics. The top 20 papers in our analysis covered a variety of topics, mainly new disease mechanisms, treatment options and risk factors for the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 30 publications
5
24
0
1
Order By: Relevance
“…The sample size calculation in bibliometric studies about citation classics as well as for articles with the highest online attention is still not determined in a standard way, although in citations studies some authors advocate the use of the h‐index as a reference (Martinez, Herrera, Contreras, Ruiz, & Herrera‐Viedma, ). The authors generally set a specific number of publications as the ideal number of “citation classics.” Most of the published Altmetric studies analysed the first 100 articles with the highest AAS (Delli, Livas, Spijkervet, & Vissink, ; Kim et al, ) although it is possible to find articles analysing 50 or 20 articles (Araujo, Sorensen, Konkiel, & Bloem, ; Barbic et al, ). Only one article about the most discussed articles on the Web in the orthodontic field included 200 articles (Livas & Delli, ) and we decided to use the same sample magnitude.…”
Section: Methodsmentioning
confidence: 99%
“…The sample size calculation in bibliometric studies about citation classics as well as for articles with the highest online attention is still not determined in a standard way, although in citations studies some authors advocate the use of the h‐index as a reference (Martinez, Herrera, Contreras, Ruiz, & Herrera‐Viedma, ). The authors generally set a specific number of publications as the ideal number of “citation classics.” Most of the published Altmetric studies analysed the first 100 articles with the highest AAS (Delli, Livas, Spijkervet, & Vissink, ; Kim et al, ) although it is possible to find articles analysing 50 or 20 articles (Araujo, Sorensen, Konkiel, & Bloem, ; Barbic et al, ). Only one article about the most discussed articles on the Web in the orthodontic field included 200 articles (Livas & Delli, ) and we decided to use the same sample magnitude.…”
Section: Methodsmentioning
confidence: 99%
“…AAS was sensitive to the latest content, and recent publications tended to receive higher AAS. For example, the Altmetric top 20 list of Parkinson's disease research published in 2017 did not include any papers that were reported to be the most [27]. However, in our report, two articles, about leisure activities and bilingualism as protective factors, were included in the top 50 list even though they were published before 2011. erefore, it was suggested that the influence of important articles through social media might be weakened, but it did not disappear even after some time.…”
Section: Discussionmentioning
confidence: 90%
“…After putting it all together, the AAS indicates a quantified approximation of all the real-time attention picked up for a research output. The score is useful when looking at several articles together in order to identify the level of online activity related with a particular research output [6][7][8]11].…”
Section: Discussionmentioning
confidence: 99%
“…Using these algorithms, they have developed an Altmetric Attention Score (AAS) for scientific articles through their website (https://www.altmetric.com). The publication of research using the AAS has increased in a variety of medical sciences [6][7][8].…”
mentioning
confidence: 99%